Assessing dispositions in pre-service teachers: does setting or experience affect dispositions? A mixed-methods study - Frederiksen, Heidi Lynne, author; Cooner, Donna D. (Donna Danell), advisor; Coke, Pamela K., committee member; Gloeckner, Gene W., committee member; Lucero, Rodrick S., committee member (Colorado State University. Libraries, 2010)
The purpose of this study was to determine whether there was a significant difference between the perceived dispositions in pre-service teachers in urban settings versus non-urban settings. It was also the intent of this study to describe the change in perceived dispositions throughout pre-service teachers' internship experiences. Graduate students (N=44) from a teacher education program participated by providing responses to surveys, reflections, and focus groups. Final Assessment (FA) grades were also gathered to validate responses. The nature of self-reported data requires this study to collect both quantitative and qualitative data so that pre-service teachers' responses can be validated with their experience, which influenced the decision to employ a mixed-methods design for this study. A triangulation mixed methods design (QUANT + QUAL) was used. The quantitative analysis used a non-experimental comparative approach. Inductive within deductive coding was used to analyze the journal responses and focus groups. Template analysis (King, 2004) used pre-established codes based on the 10 INTASC Principles and Dispositions Indicators (1992). Themes also emerged inductively and were identified throughout the coding process. Data were analyzed based on time of response (fall and spring), internship setting (urban or non-urban), and instructional setting (urban or non-urban). No statistically significant changes in dispositions were found between urban and non-urban internship settings. However, differences were found in the qualitative results when instructional settings were analyzed. The urban setting participants showed preferences for Principles 2: Child Development and Learning Theory, 3: Learning Styles and Diversity and 5: Motivation and Behavior, while the non-urban setting preferred Principles 3: Learning Styles and Diversity and 4: Instructional Strategies and Problem Solving. Principle 10: Interpersonal Relationships showed equal preference among participants in both instructional and internship settings. Seven out of the ten INTASC Principles showed significant differences over time; five showed decreases in response, while two showed increases. The following principles showed changes: Principle 4: Instructional Strategies and Problem Solving increased over time, Principle 9: Professional Growth and Reflection also showed an increase, and Principle 7: Planning for Instruction decreased. Results from this study will provide policy recommendations for teacher licensing programs on reporting to accreditation agencies and determining what programmatic components help to develop desired dispositions in pre-service teachers.
Keywords: urban education; teacher education; mixed methods; teacher dispositions; pre-service teachers; Teachers -- Training of -- Colorado; Student teachers -- Colorado -- Attitudes; Student teachers -- Colorado -- Professional ethics; Student teachers -- Colorado -- Psychology; Education, Urban -- Colorado